Fine-scale spatial and seasonal rangeland use by cattle in a foot-and-mouth disease control zones - Kaszta, Ż; Marino, J; Wolff, E (Elsevier, 2017)
Overgrazing of ranglands and foot-and-mouth disease (FMD) are persistent problems in the communal lands bordering the Kruger National Park (KNP) and the adjacent private game reserves in South Africa. Improved livestock management is needed to address these problems, and detailed understanding of cattle ranging behaviour in the FMD control zones is central to improving livestock management. We used environmental data on seasonal variation in forage quality (nitrogen content) and quantity (biomass) derived from high resolution satellite imagery, coupled with cattle GPS locations, to develop a resource utilization function of cattle space use patterns and predicted spatial patterns of their probability of occurrence in the wet and dry seasons. We calculated cattle resource utilization distributions and delineated home ranges of cattle from six villages by applying utilization kernels using the plug-in method as a bandwidth estimator. The overlap between seasonal home ranges was 61% and between core areas 49%, indicating seasonal selectivity mainly within the home ranges. Cattle selected forage with higher quantity and quality during the dry season but behaved like bulk grazers in the wet season. Furthermore, we found that herds in the dry season usually have smaller home ranges and stay closer to water sources and villages than in the wet season. Our prediction maps highlight seasonal differences in probability of cattle occurrence, with implications for rangelands management strategies to minimalize overgrazing and FMD transmission.